THE LANGUAGE OF HIGH MODERNISM AND THE FINITENESS OF ALTERITY - Kiril HADZHIKOSEV (Linguarum Universe, 2025)
The modernist literary experiment is widely credited with opening up different conceptual mechanisms whereby the other might be welcomed into the world without the risk of being appropriated by the same. In this line of thought, modernist literature can be reimagined as presenting an ethical project whose implicit aim is to dramatize the infinity of the face of the other. In Levinasian terms, the face of the other is not merely a physical appearance but an epiphany of radical alterity that disrupts the self’s self-enclosed (or finite) autonomy. This article proposes, however, that conceptualizing alterity as a form of an event within writing possesses inherent limitations. Writing for high modernists becomes more than a means of expressing the self and exploring the world; it also becomes a means of exploring both the self and the world. In going “meta,” writing becomes its own (play)ground of signification and, being thus, assumes an independent “logic” which abstracts itself from the pragmatic (or even ethical) concerns of radical alterity (the otherness of the other). In consequence, modernist writing becomes even more autonomous and rigid. The modernist technique of the interior monologue, therefore, turns out to be a method not only of exploring inner consciousness but also of “writing” the world and thus creating it according to an abstract set of rules and regulations (not so much unlike Heidegger). How are we to think the purported irreducibility of alterity (of the face of the other) to logic and calculability within such an artistic paradigm? This article suggests that the visible in modernist writing (especially in Joyce) becomes scriptible in implicitly recognizing that the world can be “written over” in advance, that is, a priori or through and as speech-in-writing (stylizing the self and the other through the interior monologue). Within this conceptual framework, we can situate the dynamics between the infinity of the face of the other and the finiteness of alterity as it becomes visible in writing through speech-in-writing. Hence, language becomes the means of actualizing alterity through limiting the otherness of the other in and through writing. Inner reality in this respect turns out to be a convention as much as the irreducible alterity of the face of the other is revealed to be finite in its linguistic “mode” of appearing. This leads us to a broader exploration of the repercussions of modernist experimentation with form and content within the context of mediating the world and thinking alterity.